COMPARING THE GROSS AND NET PRICE METHODS. - Park, Colin (The Accounting Review, 1952)
Accounting instruction must convey to students as many progressive ideas as possible. Simultaneously, time should be taken to show traditional practices more likely to be found in business. Thus overemphasis of new theories that limits or excludes discussion of older business procedures defrauds the student. He may be bewildered when the accounting methods which confront him in his first job are not what he has been led to expect. Unbalanced emphasis in the other direction is even less desirable for the new accountant will not have had a chance to develop in college the background for the creative thinking which can make possible his advancement to executive responsibility. A striking example of the necessity for a balanced treatment of accounting ideas is in the teaching of the net and gross price methods of recording purchases and sales. Fairly impartial presentation of these opposing methods can be achieved in a fifty-minute class period. The simple comparative illustration has been effective in presenting comprehensively both methods despite the writer's admitted preference for the net price method.